Evaluation of Diagnoses According to ICD-10 and ICPC-2 in Family Medicine Practice: A Retrospective Study - Olgun Göktaş (International Journal of Clinical Practice)
Conclusion: According to our results in family medicine practice, the equivalents of ICD-10 and ICPC-2 codes were different in number and percentage. It is ideal for individual health and research that the diagnosis codes in family medicine are the same as the codes in other secondary and tertiary care clinics. Since health requires holisticity, we recommend that both classifications be integrated and revised to be globally understandable and provide complementary coding in different clinical applications.